Heterologous expression of a novel drug transporter from the malaria parasite alters resistance to quinoline antimalarials - Tindall, Sarah M.; Vallières, Cindy; Lakhani, Dev H.; Islahudin, Farida; Ting, Kang-Nee; Avery, Simon V. (Nature Publishing Group, 2018)
Antimalarial drug resistance hampers effective malaria treatment. Critical SNPs in a particular, putative amino acid transporter were recently linked to chloroquine (CQ) resistance in malaria parasites. Here, we show that this conserved protein (PF3D7_0629500 in Plasmodium falciparum; AAT1 in P. chabaudi) is a structural homologue of the yeast amino acid transporter Tat2p, which is known to mediate quinine uptake and toxicity. Heterologous expression of PF3D7_0629500 in yeast produced CQ hypersensitivity, coincident with increased CQ uptake. PF3D7_0629500-expressing cultures were also sensitized to related antimalarials; amodiaquine, mefloquine and particularly quinine. Drug sensitivity was reversed by introducing a SNP linked to CQ resistance in the parasite. Like Tat2p, PF3D7_0629500-dependent quinine hypersensitivity was suppressible with tryptophan, consistent with a common transport mechanism. A four-fold increase in quinine uptake by PF3D7_0629500 expressing cells was abolished by the resistance SNP. The parasite protein localised primarily to the yeast plasma membrane. Its expression varied between cells and this heterogeneity was used to show that high-expressing cell subpopulations were the most drug sensitive. The results reveal that the PF3D7_0629500 protein can determine the level of sensitivity to several major quinine-related antimalarials through an amino acid-inhibitable drug transport function. The potential clinical relevance is discussed.